Postnatal corticosteroid exposure in very preterm infants: A French cohort study - Iacobelli, Silvia; Allamèle-Moutama, Käliani; Lorrain, Simon; Gouyon, Béatrice; Gouyon, Jean-Bernard; Bonsante, Francesco; , the Logipren Collaborative Working Group; Abasse, S.; Alexandre, C.; Brat, R.; Brault, D.; Brisseau, L.; et al. (Frontiers in Pharmacology, 2023)
Background: Postnatal corticosteroids (PC) are widely used in very preterm infants. International reports and national multicenter trials describe a marked variability across countries and inter-sites, in the use of PC. Few information is available on therapeutic indications and prescription characteristics of PC. Aim: The main objective of this study was to describe the exposure to PC in a large cohort of preterm infants born at less than 32 weeks of gestation, according to the prescription data of 41 tertiary-care NICUs in France. Secondary objectives were to describe therapeutic indications, day of life (DOL) of the first exposure, route of administration, duration, cumulative dose for each drug, and differences in exposure rates across centers. Methods: We conducted a prospective observational cohort analysis during five years in 41 French tertiary-care NICUs using the same computerized order-entry system. Results: In total, 13913 infants [birth weight 1144.8 (±365.6) g] were included. Among them, 3633 (26.1%) were exposed to PC, 21.8% by systemic and 10.1% by inhaled route. Within the study population, 1992 infants (14.3%) received the first corticosteroid treatment in the first week of life and 1641 (11.8%) after DOL 7. The more frequent indications were prevention and/or treatment of bronchopulmonary dysplasia, and arterial hypotension. Hydrocortisone was the more often prescribed molecule. For systemic PC the first exposure occurred in mean at DOL 8.4 (±13.5), mean duration of treatment was 10.3 (±14.3) days, and the cumulative dose (expressed as the equivalent dose of hydrocortisone) was in median 9.0 mg/kg [0-396]. For inhaled PC, the first exposure occurred in mean at DOL 33.1 (±19.7), and mean duration of treatment 28.5 (±24.4) days. The exposure rate ranged from a minimum of 5% to a maximum of 56% among centers, and significantly increased over the study period (p<0.0001). Conclusions: In this French cohort of very preterm infants, around one patient out to five was exposed to PC during hospital stay in the NICU. The exposure occurred early, starting from the first week of life. Exposure rate widely varied among centers. Pharmacoepidemiology studies are useful to increase knowledge on corticosteroid utilization patterns in preterm infants.